Klientela : nieformalne systemy wladzy w Polsce i Europie XVI-XVIII w. - Maczak, Antoni (Warszawa : Semper, 1994)
The history of the rise of the political institution in Europe and in Poland.
Includes bibliographical references (p. 307-346) and index.
Keywords: Patron and client -- Europe -- History; Patron and client -- Poland -- History; Elite (Social sciences); Power (Social sciences); Europe -- Social conditions; Poland -- Social conditions